2020
DOI: 10.1371/journal.pone.0233745
|View full text |Cite
|
Sign up to set email alerts
|

Presence of small resistant peptides from new in vitro digestion assays detected by liquid chromatography tandem mass spectrometry: An implication of allergenicity prediction of novel proteins?

Abstract: The susceptibility of newly expressed proteins to digestion by gastrointestinal proteases (e.g., pepsin) has long been regarded as one of the important endpoints in the weight-of-evidence (WOE) approach to assess the allergenic risk of genetically modified (GM) crops. The European Food Safety Authority (EFSA) has suggested that current digestion study protocols used for this assessment should be modified to more accurately reflect the diverse physiological conditions encountered in human populations and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 50 publications
(55 reference statements)
2
13
0
Order By: Relevance
“…The addition of DTT was vital for avoiding disulfide bond formation, and the addition of BSA was found necessary to keep CARM1 in its active form by blocking aggregation and reducing unspecific binding of the CARM1 to the well plate. Sample workup consisted of quenching the enzyme reaction by the addition of 0.1% formic acid solution (known to be compatible with the MS conditions of the assay 28 ) and addition of the internal standard.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The addition of DTT was vital for avoiding disulfide bond formation, and the addition of BSA was found necessary to keep CARM1 in its active form by blocking aggregation and reducing unspecific binding of the CARM1 to the well plate. Sample workup consisted of quenching the enzyme reaction by the addition of 0.1% formic acid solution (known to be compatible with the MS conditions of the assay 28 ) and addition of the internal standard.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Increasingly, the evidence surrounding the allergenicity risk assessment for GM crops indicates that digestion assays are of little value in the context of protein allergenicity. Recent advancements in using MS to identify small peptides in digesta has not improved the value of digestion assays for the assessment of allergy risk (Mackie et al, 2019 ; Wang et al, 2020 , 2021 ). Therefore, the weight of the current evidence surrounding the allergenicity risk assessment for GM crops suggests that digestion assays should not be considered unless a validated assay with proven criteria is developed that can distinguish allergens from non-allergens with some reasonable level of reliability (Verhoeckx et al, 2019 ; Herman et al, 2020 ; Bøgh and Madsen, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Technical advancements in the application of mass spectrometry (MS) to identify small peptides in complex mixtures have been used to characterize the processing of known allergens and non-allergens exposed to digestive enzymes (Mackie et al, 2019 ; Korte et al, 2017 ; EFSA Panel on Genetically Modified Organisms et al, 2017; Wang et al, 2020 ; Di Stasio et al, 2020 ). No pattern of peptide fragmentation was found to be associated with the allergenic status of proteins (Torcello-Gómez et al, 2020 ; Wang et al, 2020 ). MS can be useful in the identification of epitopes contained in small peptides within the digestive residues of known allergens, which can then be further investigated using IgE antibodies from sensitized individuals, but such analyses are incapable of identifying unknown allergenic epitopes in proteins not known to cause allergy.…”
Section: Mass Spectrometric Detection Of Small Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pepsin resistance test is performed regularly, although several studies have demonstrated that there is a poor correlation between resistance to pepsin digestion and allergenicity (Kenna and Evans, 2000 ; Fu et al, 2002 ; Takagi et al, 2003 ; Thomas et al, 2004 ; Herman et al, 2007 ; Ofori‐Anti et al, 2008 ; Costa et al, 2020). In contrast, other studies show that the classical pepsin resistance assay and simple SDS–PAGE analysis, as developed by Astwood et al ( 1996 ), can distinguish between pepsin susceptible and resistant proteins and remains as the most useful assessment of the potential exposure of an intact newly expressed protein as part of product safety assessment within a weight‐of‐evidence approach (Wang et al, 2017 , 2020 ). However, these studies only used small sets of proteins and a larger reference set is needed to make definite conclusions on the predictability of digestion tests.…”
Section: Assessmentmentioning
confidence: 99%